2006
DOI: 10.1007/s00774-005-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Notch signaling in initiation of prechondrogenic condensation and nodule formation in limb bud micromass cultures

Abstract: Notch signaling is an evolutionarily conserved mechanism that plays a critical role in the determination of multiple cellular differentiation pathways and morphogenesis during embryogenesis. The limb bud high-density culture is an established model that recapitulates mesenchymal condensation and chondrocyte differentiation. Reverse transcription-polymerase chain reaction (RT-PCR) showed that Notch and its related genes were expressed in such cultures on day 1 and reached a peak between day 3 and day 5, when ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 40 publications
7
42
0
1
Order By: Relevance
“…DAPT treatment significantly enhanced cartilage nodule formation ( Fig. 2A), suggesting that Notch inhibition accelerates commitment of MPCs to the chondrocyte lineage, a finding that is consistent with a prior study (Fujimaki et al, 2006). We also assessed the effect of DAPT on the expression of the chondrogenic markers Sox9, Col2a1 and Agc1 via real-time RT-PCR.…”
Section: Notch Signaling Is a General Regulator Of Mpc Differentiationsupporting
confidence: 86%
“…DAPT treatment significantly enhanced cartilage nodule formation ( Fig. 2A), suggesting that Notch inhibition accelerates commitment of MPCs to the chondrocyte lineage, a finding that is consistent with a prior study (Fujimaki et al, 2006). We also assessed the effect of DAPT on the expression of the chondrogenic markers Sox9, Col2a1 and Agc1 via real-time RT-PCR.…”
Section: Notch Signaling Is a General Regulator Of Mpc Differentiationsupporting
confidence: 86%
“…Fusion of primordia might reflect a dynamic requirement of Notch signalling for the maintenance of the dermal condensation. The most common hypothesis of the role of the Notch system in boundary formation and in segregation of one cell type from another has been previously described in other models such as axial skeletal formation (Bulman et al, 2000) and chondrogenesis (Fujimaki et al, 2006). Here we show that Notch signalling appears to be implicated not in the initial choice between the two fates of embryonic skin, but in a later step to allow stabilization of the newly formed pattern.…”
Section: Discussionsupporting
confidence: 62%
“…There are, however, several cell culture studies showing that Notch signaling functions as an inhibitor of the early stage of chondrocyte differentiation (13,27,28). In vivo studies on genetic gain-and loss of function of the signaling using paired-related homeobox gene 1 (Prx1) promoter-driven Cre-transgenic (Prx1-Cre) mice also showed that activation of Notch receptors and RBPjκ in mesenchymal progenitor cells inhibited their differentiation into chondrocytes and osteoblasts, and thereby suppressed cartilage and bone formation, respectively (29,30).…”
Section: Discussionmentioning
confidence: 99%